Strategi Penguatan Database Nasabah Pada Perbankan Syariah - Tri Ibnu Ramadhanu; Syahrul Tanjung; Heri Yunus; Habibul Ahir; Nurbaiti (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Potential cyber attacks the financial sector, particularly banking, is the most vulnerable to such threats. The most common attacks include phishing and ransomware, as experienced by PT. Bank Syariah Indonesia in May 2023, where 15 million pieces of data belonging to customers and employees were stolen by the Lockbit 3.0 ransomware hacking group. The aim of this study is to provide a strategy concept for strengthening customer databases in Islamic banking, which can serve as a reference for Islamic banking institutions in the future to address cyberattacks. This research employs a qualitative method with a descriptive approach. The study identifies three strategies for enhancing customer databases in Islamic banks: Data backup, Banking technology architecture, and Government regulations. With a strong database in place, the trust entrusted to Islamic banks can be upheld. The author recommends that the government formulate specific legislation regulating internet banking to safeguard the security of the Sharia Banking databases.